Eruption - Smith, Roland, 1951- (Smith, Roland, 1951- Storm runners., 2012)
Twelve-year-old Chase and his friend Nicole Rossi attempt to rescue the Rossi Brothers' Circus--lions, tigers, elephants, and all--in Mexico, where a massive earthquake has struck, leading to the imminent eruption of a volcano.